Does aortic pulse wave velocity have any prognostic significance in advanced heart failure patients? - Abolfazl Dohaei; Sepideh Taghavi; Ahmad Amin; Shahin Rahimi; Nasim Naderi (Journal of Cardiovascular and Thoracic Research, 2017)
Introduction: Noninvasive measurement of arterial stiffness by pulse-wave velocity (PWV) has prognostic value in different sub groups of cardiovascular disorders. We aimed to measure the PWV in advanced heart failure (HF) patients with reduced left ventricular ejection fraction (LVEF) and investigate whether it has any prognostic significance in this group of patients. Methods: Between 2013 to 2015 patients with a diagnosis of advanced HF (LVEF ≤ 30%) scheduled for right heart catheterization (RHC) were included in our study. PWV was measured before RHC in each patient using vascular explorer device (Enverdis GmbH) in catheterization laboratory. The patients were subsequently followed for 6 months and their hospitalization or death (composite of all-cause death/hospitalization) were recorded. Results: A total of 50 patients (38 men) were enrolled. The mean (SD) of age was 45 (16) years. The mean PWV was 6.8 m/s. There was no statistically significant correlation between the PWV and the clinical, echocardiographic and RHC data. The PWV was not different in patients with or without composite of all-cause death/hospitalization (7.3 versus 6.3, P > 0.05). In this study cardiac output (CO) (beta = -0.53, P = 0.02, odds ratio = 0.6, 95% CI = 0.4-0.9), pulse pressure (PP) (beta = -0056, P = 0.03, odds ratio=0.95, 95% CI = 0.89-0.99) and age (beta = -0.045, P = 0.05, odds ratio=0.96, 95% CI = 0.9-1.001) were independent predictors of composite of all-cause death/hospitalization. Conclusion: In patients with advanced systolic HF, PWV may not be a good prognostic factor and does not have any added value over previous well known prognostic factors.